The provision of dietary animal fibre for captive tigers (Panthera tigris): implications for animal welfare and gastrointestinal health - Esparza Guerrero, Karla Cristina (2021)
Previous research has demonstrated that poorly digestible components of whole prey such as tendons, ligaments, fur, and skin (i.e. animal fibre) can positively influence the health and welfare of strict carnivores. Through non-invasive methods, the impact of dietary animal fibre was assessed in captive tigers using two common North American diets: (1) 100% commercial raw horsemeat, compared with (2) the same raw horsemeat (80%) with added whole prey (20%). A randomised crossover study was performed over 8-week periods with eight animals. Faecal consistency, pH, fermentation profiles (short-chain fatty acids and end-product concentrations), time of first appearance, and total tract apparent macronutrient digestibility were employed as gastrointestinal (GI) functional parameters. Two faecal inflammatory biomarkers, N-methylhistamine and S100A12, were measured as non-invasive GI health indicators. Finally, behavioural time budget and faecal glucocorticoid metabolites were evaluated as part of the welfare assessment. An inclusion rate of 20% whole prey was insufficient to elicit any changes in the parameters measured. No significant differences in GI functional or health parameters or welfare indicators were detectable between dietary conditions. One exception was the faecal consistency score; tigers fed the diet with added whole prey exhibited significantly lower values. However, the mean scores for the tigers on each of the two diets were considered ideal for the species. Given the lack of impact seen in the suite of GI parameters, this suggests that the difference was of limited biological importance and highlights the need to use a panel of measures when evaluating dietary interventions. As part of the holistic assessment approach of this study, behavioural and physiological welfare indicators were used to investigate dietary impacts beyond the GI tract. Aligning with the GI findings, both welfare indicators similarly supported a lack of dietary effect. Diets incorporating ≤ 20% whole prey are unlikely to promote any of the previously reported benefits as seen in other felid species fed higher fibre concentrations. Future research should evaluate a wider range of inclusion rates, different types of whole prey and/or fibre sources. The results from this study clearly demonstrate the importance of using multiple integrated indicators rather than single isolated parameters to ensure a comprehensive evaluation of the dietary impact on animal health and welfare.